Utility and Outcome of Angioembolization for High-Grade Renal Trauma Management in a Large Hospital-Based Trauma Registry. Issue 5 (4th May 2022) - Hakam, Nizar; Amend, Gregory M.; Nabavizadeh, Behnam; Allen, I. Elaine; Shaw, Nathan M.; Cuschieri, Joseph; Wilson, Mark W.; Stein, Deborah M.; Breyer, Benjamin N.
Abstract : Purpose: We evaluated angioembolization (AE) use for high-grade renal trauma (HGRT) management and compared AE vs surgical repair (SR) in requiring nephrectomy. Materials and Methods: Using National Trauma Data Bank® 2013–2018, we identified patients with HGRT who underwent AE or SR as initial management. Therapy failure was defined as performing subsequent nephrectomy, partial nephrectomy, SR or AE. Logistic regression was performed to assess the association between intervention type (AE vs SR) and nephrectomy. Analysis was repeated in a propensity score-matched cohort constructed by matching AE to SR patients on American Association for the Surgery of Trauma (AAST) grade, injury mechanism (blunt vs penetrating) and hemodynamic instability (systolic blood pressure <90 mmHg). Results: There were 266 patients in the AE group and 215 in the SR group. Median age was 29.5 years and 212 patients (44.1%) had penetrating injuries. AE was successful in 94.2% and 85.3% of grade IV and V injuries, respectively, whereas SR was successful in 82.1% and 56%, respectively. Grade V injury was associated with AE failure in the adjusted analysis (OR 3.55, 95% CI 1.22–10.2, p=0.02). Nephrectomy was less likely to be performed after AE vs after SR in HGRT (6.4% vs 17.2%, p=0.01), AAST grade IV (4.2% vs 13.7%, p=0.001) and AAST grade V (12% vs 44%, p=0.001). The matched cohort comprised 528 patients. In post-match regression, AE, compared to SR, was associated with lower odds of nephrectomy (OR 0.18, 95% CI 0.04–0.70, p=0.013). Conclusions: AE achieved superior kidney salvage compared to SR in this observational cohort. These results inform both clinical practice and future prospective trials.